Perbandingan Pengaturan Mengenai Perlindungan Hukum Terhadap Invensi Di Bidang Teknologi Informasi Dan Komunikasi Antara Indonesia Dengan Jepang - Atsar, Abdul (UI Scholars Hub, 2017)
This paper discusses the comparison between legal protection arrangements of invention in the field of Information and Communication Technology (ICT) in this case is software (software) especially patent. Japanese Patent Law explicitly regulates software (software) as a patentable subject. Whereas Law no. 28 Year 2014 on Copyright stipulates that the software can still be protected if Patent protection already exists from the country of origin. Using a comparative study of this paper can be one of the reference in legal protection to answer the rapid development of information and communication technology.